An Analysis of Inclusive Leadership and Career Patterns on Employee Performance with Work-Life Balance as an Intervening Variable - Asmoro, Wanda Prihanto; Kirana, Kusuma Chandra; Hadi, Syamsul (JURNAL MANAJEMEN MOTIVASI, 2025)
Inclusive leadership and career path are two crucial factors in improving employee performance, particularly in the insurance sector such as at PT. Jasa Raharja Kepulauan Riau. This study aims to analyze the influence of both variables on employee performance, with work-life balance as a mediating variable. A quantitative method with a saturated sampling technique was used, involving 11 employees as respondents. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to examine the relationships between variables. The results show that inclusive leadership has a positive but not significant effect on employee performance, yet has a significant positive effect on work-life balance. Meanwhile, career path has a significant positive effect on both employee performance and work-life balance. Furthermore, work-life balance significantly influences employee performance and serves as a mediating variable between inclusive leadership and employee performance. However, it does not mediate the relationship between career path and employee performance. Management is advised to enhance inclusive leadership, structured career development, and work-life balance programs to boost employee performance. Further research is recommended to explore other potential mediating variables for a more comprehensive understanding